Fatty Acid Profile and Squalene Content in Cucumber Seed Oil (Cucumis sativus) - Soetjipto, Hartati; Febriyanti, Teresa; Kristijanto, Agus Ign. (Molekul, 2023)
Cucurbitaceae is known as a source of vegetable oil that can be used in the fields of food, medicine, and cosmetics. Several studies showed that vegetable oil from the Cucurbitaceae contains squalene. Squalene is a high-economic value compound that was originally found in shark liver oil. This compound is proven to be very beneficial for health and cosmetics. The objectives of the study are to determine the fatty acid profile and squalene content of cucumber seed oil using the Gas Chromatography-Mass Spectrometry (GC-MS) method. Starting with the preparation of cucumber seeds by drying the clean seed in an oven at 60 0C for 1 hour, then the seeds were extracted using 2 methods namely maceration and a continuous extraction method with a soxhlet extractor. The yield of crude oil obtained by the soxhlet extractor is higher than maceration, which was 19.38 ± 0.94%, yellow colour, and distinct aroma, 2% water oil content; oil density of 0.96 g/mL; free fatty acid levels of 3.51%; an acid value of 4.97 mg NaOH/g oil; and peroxide value of 0.82 meq O2/g oil. The results of the GC-MS analysis showed that cucumber oil was composed of 3 main components namely palmitic acid, linoleic acid, and squalene. Keywords: Cucumber seed oil, Cucumis sativus, fatty acids, squalene.